Effects of school environment on depression among Black and White adolescents. Issue 3 (9th December 2022) - Choi, Mi Jin; Hong, Jun Sung; Travis, Raphael; Kim, Jangmin
Abstract: While the school environment is critical for adolescents' psychological development, how the school environment influences depression among different racial groups has not been fully explored. This study aims to identify the effects of the school environment (school connectedness, school climates, trouble with peers and teachers) on depressive symptoms among Black and White adolescents. It also compares how the effects of school environments differ between Black and White adolescents. This study analyzed wave 6 of the Fragile Families and Child Well‐being Study, a longitudinal birth cohort study in 20 major cities across the United States. Almost three‐fourth (73.39%) of the adolescents were Black, and 26.61% were White. About half (50.46%) of the adolescents were females, and the mean age of adolescents was 15.39. Multiple regression analysis showed that higher school connectedness and less frequent troubles with teachers were associated with lower depression among Black adolescents. In contrast, only school connectedness was associated with depression among White adolescents. Higher school connectedness was associated with lower depressive symptoms for both Black and White adolescents. However, the magnitude of the effects of school connectedness was found to be statistically weaker among Black adolescents. These findings suggest a need for creating a racially equitable school environment that makes every student feel more connected to their schools, especially Black students.